Adsorption of As on hydroxy-Fe-montmorillonite complexes - Liao, L; Fraser, D (2005)
Arsenate has high affinity for soluble hydroxy-Fe species and Fe-oxyhydroxide precipitates. In addition, the hydrolysis of Fe(III) and the growth of the initially precipitated Fe(III) phases are strongly influenced by the presence of montmorillonite. In this paper, the adsorption of As onto various hydroxy-Fe-montmorillonite (H-F-M) complexes was studied. Three systems of samples were prepared by mixing montmorillonite, hydroxy-Fe and arsenate in different sequences: (1) Prior mixing of montmorillonite and hydroxy-Fe before the addition of arsenate; (2) prior mixing of hydroxy-Fe and arsenate before the addition of montmorillonite; and (3) prior mixing of montmorillonite and arsenate before the addition of hydroxy-Fe. For each system, the effects of pH, ionic strength, temperature, initial Fe and As concentrations and adsorption duration on the overall uptake of As by H-F-M complexes were studied. Results showed that the uptake of As increased with increasing pH, temperature, initial Fe concentration and adsorption duration, and decreased with increasing ionic strength and initial As concentration to different extents for the three systems. The variation of the As uptake of H-F-M complexes with pH in the range of study is opposite to that reported previously for Fe-O-H systems in the absence of montmorillonite and similar to that reported for montmorillonite in the absence of hydroxy-Fe. The marked influence of ionic strength on the As uptake of H-F-M complexes indicates that outer-sphere complexation plays an important role. This is quite different from the adsorption of As on the surface of either Fe-oxyhydroxides or montmorillonite alone in which inner-sphere complexation dominates. Under all experimental conditions, the H-F-M complexes studied displayed a very strong affinity for As, among which system 2 had the highest As adsorption capacity and system 1 the lowest. The authors attribute this to the differences in mixing sequence which resulted in more hydroxy-Fe. (the main adsorbent for As) in system 1 adsorbing onto montmorillonite before adsorbing As than in systems 2 or 3. Copyright by Science in China Press 2005.